If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2) + 7x + -8 = 0 Reorder the terms: (2 + x) + 7x + -8 = 0 Remove parenthesis around (2 + x) 2 + x + 7x + -8 = 0 Reorder the terms: 2 + -8 + x + 7x = 0 Combine like terms: 2 + -8 = -6 -6 + x + 7x = 0 Combine like terms: x + 7x = 8x -6 + 8x = 0 Solving -6 + 8x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 8x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 8x = 0 + 6 8x = 0 + 6 Combine like terms: 0 + 6 = 6 8x = 6 Divide each side by '8'. x = 0.75 Simplifying x = 0.75
| -7(v+4)+3v+7=8v+7 | | 5r+r^2-24= | | 2x+2y+80=180 | | .33x+1.33=1-.25x+1.25 | | 2x+2-5(x+1)=5x+4 | | b^2-11b+28= | | x^3+2x^2-6x-12= | | 4x^3+5x^2-8x-10= | | 0=4+2x^2 | | -4[4-(3b+4)]=5-4(3b+9) | | 4m-2.50=14.30 | | (x+2)(x+2)+8x=0 | | 2x^8+2x^7-18x^6+10x^5= | | 0=20x-2x^2-4-2x^2 | | -4[4-(3b+4)]=7-4(3b+8) | | 5x^4y^6+10x^5y^5= | | (2ln(6x)x^2)-(x^2)= | | x-3+4x=-3+11x | | -0.09p-0.04(4-4p)=0.02(p-3)-0.1 | | -6g^6+9g^4-4g^2= | | 29x+17y=-2 | | 7(y+5)-3(y+4)=19 | | X^7-7x^6-2x^5= | | -11c-(4-2c)= | | 5x-10(x+1)=-5x+22 | | 7x^8+7x-56= | | 9(z+7)-15= | | 7y-3x+6=0 | | 6-7x=24 | | (x+3)2=16x | | 4m+23=9m-2 | | 9-5x=25x-45 |